2019
DOI: 10.1111/jcpp.13129
|View full text |Cite
|
Sign up to set email alerts
|

Parenting for Lifelong Health for Young Children: a randomized controlled trial of a parenting program in South Africa to prevent harsh parenting and child conduct problems

Abstract: Background Parenting programs suitable for delivery at scale in low‐resource contexts are urgently needed. We conducted a randomized trial of Parenting for Lifelong Health (PLH) for Young Children, a low‐cost 12‐session program designed to increase positive parenting and reduce harsh parenting and conduct problems in children aged 2–9. Methods Two hundred and ninety‐six caregivers, whose children showed clinical levels of conduct problems (Eyberg Child Behavior Inventory Problem Score, >15), were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 29 publications
1
67
0
2
Order By: Relevance
“…The exciting thing about this programme by Ward et al () is that the elements included as strategies/processes of change are very similar to those highlighted as effective in existing programmes used in HIC [see Figure (Lachman et al, ) diagram below]. This is encouraging to our understanding of programme effectiveness at the individual level.…”
Section: Is There a Value In Developing New Programmes?mentioning
confidence: 67%
See 3 more Smart Citations
“…The exciting thing about this programme by Ward et al () is that the elements included as strategies/processes of change are very similar to those highlighted as effective in existing programmes used in HIC [see Figure (Lachman et al, ) diagram below]. This is encouraging to our understanding of programme effectiveness at the individual level.…”
Section: Is There a Value In Developing New Programmes?mentioning
confidence: 67%
“…In this issue of the JCPP, Ward et al () explore the problems around design and implementation of behaviour interventions in the context of preventing child maltreatment. This intervention, the Sinovuyo Caring Family Programme, has been developed with the United Nation Sustainable Development Goal (SDG) in mind: to end all violence against children in MLICs.…”
Section: Development Of a Preventative Parenting Programme For Use Inmentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on these areas in order to synthesize patterns and identify gaps in existing community-based caregiver-and family-based mental health promotion interventions for OVC. (Bell et al, 2008;Bhana et al, 2014;Eloff et al, 2014;Puffer et al, 2016;Ward et al, 2019), relative to zero identified by reviews a decade ago (King, De Silva, Stein, & Patel, 2009;Schenk, 2009). With Schenk (2009), we acknowledge that due to ethical and practical challenges, randomization is not always possible in low-resource settings and quasiexperimental including a control group (but not randomized) is a recommended option in that case.…”
Section: Resultsmentioning
confidence: 99%